Revisiting the Concept of Vigilance - Klösch, Gerhard; Zeitlhofer, Josef; Ipsiroglu, Osman (Frontiers in Psychiatry, 2022)
Vigilance deficits can be observed after a period of prolonged, continuous wakefulness. In this context there has been extensive research targeting the impact of sleep deficits on different aspects of vigilance, but the underlying concept of vigilance was hardly ever addressed and discussed. One reason for this shortcoming is the unclear and ambiguous definition of the term vigilance, which is commonly used interchangeably with sustained attention and even wakefulness. This confusion is the result of a wide range of misleading definitions, starting in the 1940s, as psychologists redefined the concept of vigilance suggested by British Neurologist, Henry Head, in 1923. Nevertheless, the concept of vigilance is still useful and innovative, especially in treating sleep problems in children and young adults. This paper reviews the current usage of the term vigilance in sleep-wake-research and describes not only the benefits, but even more clearly, its limitations. By re-focusing on the definitions given by Henry Head, the concept of vigilance is an innovative way to gather new insights into the interplay between sleep- and daytime behaviors. In addition, future research on vigilance should consider three perspectives: 1st vigilance perceived as a process to allocate resources, 2nd vigilance associated with compensatory behaviors and 3rd the role of vigilance in human environmental interactions. This approach, understood as a conceptual framework, provides new perspectives by targeting sleep-wake behaviors as a ‘real life’ outcome measure, reflecting both physical and cognitive performance as well as sleep quality and quantity.